2008
DOI: 10.1158/1541-7786.mcr-08-0034
|View full text |Cite
|
Sign up to set email alerts
|

17-Allylamino-17-Demethoxygeldanamycin Down-Regulates Hyaluronic Acid–Induced Glioma Invasion by Blocking Matrix Metalloproteinase-9 Secretion

Abstract: Hyaluronic acid (HA) has been implicated in cell adhesion, motility, and tumor progression in gliomas. We previously reported that HA stimulates secretion of matrix metalloproteinase-9 (MMP-9) and induces glioma invasion. However, the molecular mechanism of HA action and therapeutic strategies for blocking HA-induced MMP-9 secretion remain unknown. Here, we report that the Hsp90 inhibitor 17-allylamino-17-demethoxygeldanamycin (17-AAG) blocks MMP-9 secretion and that HA-induced nuclear factor-KB (NF-KB) activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…NF-kB activity is regulated by the endogenous inhibitor, IkBα, and interaction with IkBα blocks the nuclear localization of NF-kB, keeping NF-kB it sequestered in the cytoplasm. In the current study we showed that EGF induced phosphorylation of IkB, which led to degradation of IkBα and to NF-kB nuclear translocation and transcriptional activation in A431 cells (Kim et al, 2008).…”
Section: Discussionsupporting
confidence: 48%
“…NF-kB activity is regulated by the endogenous inhibitor, IkBα, and interaction with IkBα blocks the nuclear localization of NF-kB, keeping NF-kB it sequestered in the cytoplasm. In the current study we showed that EGF induced phosphorylation of IkB, which led to degradation of IkBα and to NF-kB nuclear translocation and transcriptional activation in A431 cells (Kim et al, 2008).…”
Section: Discussionsupporting
confidence: 48%
“…miR-21 facilitates glioma invasion through Ras/MAPK signaling Previously, we demonstrated that ERK1/2 and NF-kB signalings have important roles in HA-induced invasion of glioma cells lacking functional PTEN (Park et al, 2002;Kim et al, 2005Kim et al, , 2008. To examine the role of miR-21 in these pathways, we performed immunoblot analyses using relevant antibodies.…”
Section: Ha-induced Mir-21 Facilitates Glioma Invasionmentioning
confidence: 99%
“…Glioma invasion assays were performed using modified Boyden chambers with polycarbonate nucleopore membranes (Corning, Corning, NY, USA), as described previously (Park et al, 2002;Kim et al, 2005Kim et al, , 2008. Invasiveness was determined by counting cells in five microscopic fields per well, and the extent of invasion was expressed as the average number of cells per microscopic field.…”
Section: Invasion Assaysmentioning
confidence: 99%
See 2 more Smart Citations